عناية المغاربة بالسيرة النبوية (كتاب الشمائل أنموذجًا): Moroccan People's Attention to the Prophet's Sirah (Study of the Kitab of al-Syama’il al-Muhammadiyyah) - Murad Zahwi (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2022)
This study aims to find out how the Moroccan community pays attention to the sirah nabawiyyah, specifically in the book of al-Syamā'il al-Muḥammadiyyah. This study uses a qualitative method with a descriptive analytical and historical approach. The results showed that among the forms of Moroccan people's attention to the sirah of the Prophet Muhammad especially the book of al-Syamā'il al-Muḥammadiyyah is the number of syurūḥ (explanations) of the Moroccans to the book of al-Syamā'il al-Muḥammadiyyah as evidence of their attention to the book. The book of al-Syamā'il al-Muḥammadiyyah by al-Tirmiżī is one of the most important references to get to know the figure of the Prophet because it has contained everything related to his character, character and physical. Al-Tirmiżī strongly maintains the validity of the hadith and is committed to the validity of the hadith he narrates